2011
DOI: 10.1007/s00420-011-0638-3
|View full text |Cite
|
Sign up to set email alerts
|

An effectiveness evaluation of a multifaceted preventive intervention on occupational injuries in foundries: a 13-year follow-up study with interrupted time series analysis

Abstract: The intervention showed effectiveness in reducing OI rates and in improving quantitative and qualitative outcomes in two representative foundries. Challenges and limitations of interventions to assess effectiveness in preventing OI were evaluated and solutions applied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…These interventions involved, among others, the introduction of mechanical lifting equipment and employee training [48], improvements of machine performance and communication between workers and supervisors [49], reduction of lifting loads and rotation schedules [50], increased compliance with the use of protective substances and establishment of improved control procedures of occupational risks [51], improvement of technical equipment and health surveillance [52], as well as substituting chemicals and increased safety guidelines in the organisation [53]. The health-related outcomes of these interventions included back pain, injuries, sick leave, blood pressure, and eczema.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These interventions involved, among others, the introduction of mechanical lifting equipment and employee training [48], improvements of machine performance and communication between workers and supervisors [49], reduction of lifting loads and rotation schedules [50], increased compliance with the use of protective substances and establishment of improved control procedures of occupational risks [51], improvement of technical equipment and health surveillance [52], as well as substituting chemicals and increased safety guidelines in the organisation [53]. The health-related outcomes of these interventions included back pain, injuries, sick leave, blood pressure, and eczema.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, four out of ten low evidence studies reported statistically significant changes in outcomes such as self-rated health [63] and injury rates [48,52,64]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Manufacturing had the largest number of included studies: two RCTs [30,31], three CBAs [36][37][38] (one of which was removed from narrative synthesis due to critical risk of bias [36]), three ITS studies [40,42,43], and four uCBAs [48,[54][55][56]. Of which, all of the RCT and CBA studies, one of the ITS studies [42], and two of the uCBA studies [54,55] showed significant injury reductions. Interestingly, one commonality among the majority of effective interventions in manufacturing was that they employed either multifactorial approaches or educational methods that were not purely didactic [30,31,38,42,54,55].…”
Section: Manufacturingmentioning
confidence: 99%
“…Of which, all of the RCT and CBA studies, one of the ITS studies [42], and two of the uCBA studies [54,55] showed significant injury reductions. Interestingly, one commonality among the majority of effective interventions in manufacturing was that they employed either multifactorial approaches or educational methods that were not purely didactic [30,31,38,42,54,55]. Despite the possibility of cross-contamination favoring the controls, these interventions still resulted in significantly positive results, which may indicate that such efforts are especially effective.…”
Section: Manufacturingmentioning
confidence: 99%